The artist can't escape: The artist as (reluctant) public pedagogue. (May 2016) - Caris, Arthur; Cowell, Gillian
This article addresses the question of how artists may recognise art as a public pedagogy whilst staying detached from the role of teacher in the traditional sense. We report on three art practices of citizens engaging in 'situation art' to support and illustrate a few theoretical concepts derived from Biesta's theory of public pedagogy. The examples will be investigated as pedagogies 'that enact a concern for publicness', where Biesta argues for pedagogic interventions that make action possible in an arena of plurality and diversity. Inspired by Biesta we will develop the concept of 'artistic citizenship', a practising of citizenship in community settings that engages in playful and unknowable-in-advance artistic interventions in everyday life, thereby testing the quality of the public sphere and setting conditions for pedagogies that have the potential to be 'politically significant'.